SAT0438 Radiographic Involvement of Metacarpophalangeal Joints in Hand Osteoarthritis. (10th June 2014) - Addimanda, O.; Cavallari, C.; Pignotti, E.; Pulsatelli, L.; Mancarella, L.; Punzi, L.; Fioravanti, A.; Meliconi, R.
Abstract : Background: Increasing attention is being paid on metacarpophalangeal (MCP) joint involvement in hand osteoarthritis (HOA), using ultrasound (US) and magnetic resonance (MR) imaging techniques in order to detect pathologic features.(1-2) Objectives: Detailed radiographic characterization of MCPs in erosive and non erosive HOA and re-evaluation after four year follow-up period. Methods: We enrolled 368 consecutive outpatients (25 males, 6.8%) at three rheumatology centres between May 2004 and May 2006. All patients were diagnosed according to American College of Rheumatology Criteria for Hand Osteoarthritis and underwent radiographic evaluation. Each joint was graded according to Kellgren & Lawerence, and Kallman scores; Osteophyte and Joint Space Narrowing (JSN) scores according to the OARSI Atlas. In addition marginal bone erosions were also evaluated. According to the presence of Central Erosions (CE) in interphalangeal joints, patients (pts) were divided into 3 groups: NE (no CE) =129 pts (35%), E1 (one CE) =41 pts (11.2%), E2 (two or more CE) =198 pts (53.8%). Among them 44 pts (5 males, 11.4%) were re-evaluated after a period of about four years of follow-up. Results: Mean age was found to be significantly different in the three groups; age at disease onset was significantly younger in E2 patients. (see table) Mild score values for all items were obtained: no significant differences were detected among the three groups except for a significant progressive increase of JSN score from NE to E2 [mean ± sd per patient values NE =1.8±2.3 (1.4-2.3), E1 =2.4±2.5 (1.6-3.2), E2 =3.1±3.2 (2.6-3.2), p<0.0005]. No significant differences were found in the severity of radiographic damage among the ten MCPs. Marginal erosions were rarely found with percentages of positivity ranging from 3% (2nd right MCP) to 11% (4th right MCP) - mean percentage being 6.7%. At follow-up evaluations, we observed that one NE pt progressed to E2 group and 10 E1 pts progressed to E2 group. All radiographic features significantly worsened both at patient and at joint level, without significant differences among the three groups. Conclusions: MCP joints involvement is generally mild and, except for JSN, not related to the presence of erosive disease. Follow-up evaluations showed a progressive increase in all radiographic features, without differences among the groups References: Iagnocco A, Conaghan PG, Aegerter P, et al. The reliability of musculoskeletal ultrasound in the detection of cartilage abnormalities at the metacarpo-phalangeal joints. Osteoarthritis Cartilage 2012;20:1142-6. Vlychou M, Koutroumpas A, Alexiou I, et al. High-resolution ultrasonography and 3.0T magnetic resonance imaging in erosive and nodal hand osteoarthritis: high frequency of erosions in nodal osteoarthritis. Clin Rheumatol 2013;32:755-62. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2045